2022
DOI: 10.5194/acp-22-5925-2022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of convection on the upper-tropospheric O<sub>3</sub> and NO<sub><i>x</i></sub> budget in southeastern China

Abstract: Abstract. Thunderstorms can significantly influence the air composition via strong updraft and lightning nitrogen oxides (LNOx). In this study, the ozonesondes and TROPOMI (TROPOspheric Monitoring Instrument) nitrogen dioxide (NO2) observations for two cases are combined with a model to investigate the effects of typical strong convection on vertical redistribution of air pollutants in Nanjing, southeastern China. The ozonesonde observations show higher O3 and water vapor mixing ratios in the upper troposphere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Recent LNO x estimates based on satellite instruments suggest that the LNO x PE per flash falls at the lower end of the range of estimations reported in literature (100–400 mol NO x per flash) (Beirle et al., 2004; Schumann & Huntrieser, 2007). In particular, LNO x estimates based on TROPOMI NO 2 retrieval, the most modern global air quality satellite in operation, have produced LNO x PE estimates of 175 ± 100 mol and 120 ± 65 mol NO x per flash in the United States of America (USA) (Allen, Pickering, Bucsela, et al., 2021) by using lightning measurements from the Geostationary Lightning Mapper (GLM) and the Earth Networks Global Lightning Network (ENGLN), respectively, 58 ± 44 mol NO x per flash in the Ebro Valley and the Pyrenees (Pérez‐Invernón et al., 2022), and 60 ± 33 mol NO x per flash in southeastern China (Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent LNO x estimates based on satellite instruments suggest that the LNO x PE per flash falls at the lower end of the range of estimations reported in literature (100–400 mol NO x per flash) (Beirle et al., 2004; Schumann & Huntrieser, 2007). In particular, LNO x estimates based on TROPOMI NO 2 retrieval, the most modern global air quality satellite in operation, have produced LNO x PE estimates of 175 ± 100 mol and 120 ± 65 mol NO x per flash in the United States of America (USA) (Allen, Pickering, Bucsela, et al., 2021) by using lightning measurements from the Geostationary Lightning Mapper (GLM) and the Earth Networks Global Lightning Network (ENGLN), respectively, 58 ± 44 mol NO x per flash in the Ebro Valley and the Pyrenees (Pérez‐Invernón et al., 2022), and 60 ± 33 mol NO x per flash in southeastern China (Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…PE estimates of 175 ± 100 mol and 120 ± 65 mol NO x per flash in the United States of America (USA) (Allen, Pickering, Bucsela, et al, 2021) by using lightning measurements from the Geostationary Lightning Mapper (GLM) and the Earth Networks Global Lightning Network (ENGLN), respectively, 58 ± 44 mol NO x per flash in the Ebro Valley and the Pyrenees (Pérez-Invernón et al, 2022), and 60 ± 33 mol NO x per flash in southeastern China (Zhang et al, 2022). Some studies based on laboratory discharges have reported a positive relationship between the flash energy and the production of LNO x (Allen, Pickering, Lamsal, et al, 2021;Stark et al, 1996;Wang et al, 1998).…”
mentioning
confidence: 99%
“…Therefore, it is essential to distinguish the contributions of meteorological parameters and emission change firstly, and then to figure out the O3 formation mechanisms and sensitivity. Unfavorable meteorological condition was often considered to be the key factor for the O3 increase (Yin et al, 2021;Zhang et al, 2022b). Gong et al (2018) revealed that daily maximum temperature was major driving factor responsible for the national O3 pollution.…”
Section: Introductionmentioning
confidence: 99%